The Inducible Nitric-oxide Synthase (iNOS)/Src Axis Mediates Toll-like Receptor 3 Tyrosine 759 Phosphorylation and Enhances Its Signal Transduction, Leading to Interferon-β Synthesis in Macrophages - Hsieh, Ming-Yu (American Society for Biochemistry and Molecular Biology, 2014)
Double-stranded RNA (dsRNA) induces phosphorylation of Toll-like receptor 3 (TLR3) at tyrosine 759 and subsequently triggers signaling pathways to promote interferon-β (IFN-β) production. In this study, we found that dsRNA stimulation induces biphasic TLR3 Tyr-759 phosphorylation in macrophages. In addition to the immediate TLR3 Tyr-759 phosphorylation, we identified a second wave of Tyr-759 phosphorylation accompanied by an increase of both Src and ifn-β transcription in the later phase of dsRNA stimulation. Interestingly, Src phosphorylated TLR3 Tyr-759 in vitro and in vivo. However, knockdown of Src abolished the late phase of TLR3 Tyr-759 phosphorylation and decreased the nuclear accumulation of interferon regulatory factors 3 and 7 (IRF3 and -7) and IFN-β production. Reintroduction of Src restored all of these molecular changes. Notably, via down-regulation of Src, dsRNA-elicited TLR3 Tyr-759 phosphorylation, the nuclear accumulation of IRF3/IRF7, and IFN-β generation were inhibited in inducible nitric-oxide synthase (iNOS)-null macrophages. TLR3 knockdown destabilized Src and reduced the nuclear level of IRF3/IRF7 and IFN-β production in macrophages exposed to LPS (a TLR4 ligand known to induce Src and IFN-β expression). Ectopic expression of wild type TLR3, but not its 759-phenylalanine mutant, restored Src activity and ifn-β transcription. Taken together, these results suggested an essential role of the iNOS/Src/TLR3 axis in IFN-β production in macrophages.